2017
DOI: 10.1038/s41598-017-05592-7
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome – Predictable from brain imaging data

Abstract: Takotsubo syndrome (TTS) is characterized by acute left ventricular dysfunction, with a hospital-mortality rate similar to acute coronary syndrome (ACS). However, the aetiology of TTS is still unknown. In the present study, a multivariate pattern analysis using machine learning with multimodal magnetic resonance imaging (MRI) data of the human brain of TTS patients and age- and gender-matched healthy control subjects was performed. We found consistent structural and functional alterations in TTS patients compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 54 publications
3
36
1
3
Order By: Relevance
“…Both the basal ganglia and hippocampus are components of the limbic system, which is associated with emotion and sympathetic activation, while the brainstem contains the sympathetic central nucleus and the origins of descending sympathetic nerves. In 2017, Klein et al similarly demonstrated specific homogeneous anatomical and neurophysiological features in brain regions mainly associated with the control of heart functions in patients with TTS [46]. In 2018, Hiestand et al used magnetic resonance imaging to reveal structural and connective differences in the limbic networks of TTS patients and healthy subjects.…”
Section: Brain-heart Connection In Takotsubo Syndromementioning
confidence: 99%
“…Both the basal ganglia and hippocampus are components of the limbic system, which is associated with emotion and sympathetic activation, while the brainstem contains the sympathetic central nucleus and the origins of descending sympathetic nerves. In 2017, Klein et al similarly demonstrated specific homogeneous anatomical and neurophysiological features in brain regions mainly associated with the control of heart functions in patients with TTS [46]. In 2018, Hiestand et al used magnetic resonance imaging to reveal structural and connective differences in the limbic networks of TTS patients and healthy subjects.…”
Section: Brain-heart Connection In Takotsubo Syndromementioning
confidence: 99%
“…The IC may indicate how an emotional or a physical stressor trigger, reported in more than two thirds of patients with TTS, alter cardiac autonomic tone. In this respect, the mentioned study by Klein et al [3] supporting a heart-brain interaction in the pathogenesis of TTS, highlights the critical role of the IC in regulating top-down autonomic responses. (2) It is surprising that left ventricular (LV) apical ballooning during systole in TTS with unknown mechanism is accepted as typical but without argumentum so far.…”
mentioning
confidence: 87%
“…Third, in the next topic Dr. Finsterer dismisses the role of the insular cortex (IC), as proposed in our review 2 , by citing and quoting various papers, which, on the contrary, collectively favor an important role for the insula in TC. In particular, the study by Klein et al, while strongly supporting a heart‐brain interaction in the pathogenesis of TC, highlights that distinct areas of the limbic system, located in the dominant or non‐dominant hemisphere and normally involved in driving activation of sympathetic and parasympathetic systems, show substantial structural changes between patients with TC and healthy controls. However, throughout the paper, the aforementioned authors underline the important role of the IC in regulating top‐down autonomic responses.…”
mentioning
confidence: 98%